1981
DOI: 10.1159/000214403
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration of Platelet-Specific Proteins and Fibrinopeptide A in Patients with Artificial Heart Valves

Abstract: β-Thromboglobulin (βTG), platelet factor 4 (PF4), fibrinopeptide A (FPA), lactic dehydrogenase (LDH), and platelet count were evaluated in patients with bioprostheses and prosthetic heart valves. βTG and PF4 were significantly elevated in both patient groups (p < 0.001), whereas FPA was normal. There was no significant difference in plasma concentrations of βTG and PF4 between patients with prosthetic heart valves and bioprostheses. LDH levels were significantly (p < 0.001) higher and platelet count lower (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Although there was a trend to slightly higher plasma concentrations of pTG and PF4 in patients with WFBP compared to controls, there was no statistically significant difference between the two groups. Our re sults differ from those of others, who found increased platelet reactivity both in patients with mechanical and biological prostheses [6,7,11], but they are in agreement with the fact that the latter type of valve has a much lower incidence of thromboembolic complications, even without anticoagulant therapy [21,22], Prior to surgery, patients with MFBP had a mean platelet count significantly lower and a mean plasma concentration of (TTG and PF4 significantly higher than controls and patients with WFBP. These results do not seem to be influenced by the age of the pros theses: although the mean time from implan tation was significantly longer in patients with MFBP than in those with WFBP, we did not find any correlation -in agreement with others [6,8] -between platelet reactivity and age of the bioprostheses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although there was a trend to slightly higher plasma concentrations of pTG and PF4 in patients with WFBP compared to controls, there was no statistically significant difference between the two groups. Our re sults differ from those of others, who found increased platelet reactivity both in patients with mechanical and biological prostheses [6,7,11], but they are in agreement with the fact that the latter type of valve has a much lower incidence of thromboembolic complications, even without anticoagulant therapy [21,22], Prior to surgery, patients with MFBP had a mean platelet count significantly lower and a mean plasma concentration of (TTG and PF4 significantly higher than controls and patients with WFBP. These results do not seem to be influenced by the age of the pros theses: although the mean time from implan tation was significantly longer in patients with MFBP than in those with WFBP, we did not find any correlation -in agreement with others [6,8] -between platelet reactivity and age of the bioprostheses.…”
Section: Discussioncontrasting
confidence: 99%
“…In vivo platelet function studies have constantly shown platelet hyperactivity in patients with mechanical valves [6][7][8][9][10][11], whereas results for biological prostheses are contradictory: some authors report a plasma concentration of pthromboglobulin (pTG) and platelet factor 4 (PF4) not significantly different from that found in patients with mechanical valves, even in anticoagulated patients [6,7,11]; others, however, report a normal platelet ac tivity even in patients not on long-term anti coagulation [12], In a previous study, we ob served that patients with bioprostheses on long-term warfarin therapy presented PTG levels not significantly different from those of healthy controls [13].…”
Section: Introductionmentioning
confidence: 99%
“…14-16 Elevated PF-4 levels in plasma activity have been reported in numerous cases in which there is a platelet activation such as cardiovascular diseases, postoperative period, extra-corporeal circulation, inflammatory or infectious states, diabetes, polycythemia, cancers and some renal disorders. [17][18][19][20][21][22][23] The aim of this study was to determine the serum ADA enzyme and plasma platelet factor activities in patients with active pulmonary tuberculosis, HIV seropositive subjects, cancer patients (acute and chronic type lymphoblastic leukaemia) and to compare them with the results of healthy individuals.…”
Section: Introductıonmentioning
confidence: 99%
“…Although measurement of the clot formation or dissolution has provided a means to screen hemostasis and monitor anticoagulant therapy for over a quarter of a century, it suffers from many drawbacks. 8,9,11,19,26,[35][36][37][38]43,59,61,68,69,73,78,81,85,86,93,116 Most assays only identify bleeding problems and do not necessarily provide an overall hemostatic picture for a given patient, since the individual para metric alterations vary widely (for example, activa tion of factors or consumption of inhibitors). Table 5 depicts various methods that can be used to quantitate the molecular markers of hemostatic activation.…”
Section: Molecular Markers Of Hemostatic Disordersmentioning
confidence: 99%